XFEM and CZM modeling to predict the repair damage by composite patch of aircraft structures: Debonding parameters. (15th June 2021) - Bellali, Mohammed Amine; Serier, Boualem; Mokhtari, Mohamed; Campilho, Raul D.S.G.; Lebon, Frederic; Fekirini, Hamida
Abstract: In this work, a model based on the combination of two approaches XFEM and CZM, has been used to predict the damage of repairs by composite patch (patch/adhesive/plate assembly). This degradation is analyzed in terms of adhesive damage considering both initiation and propagation of interfacial debonding. The interfacial cohesive zone of the patch/adhesive/plate system is defined by its cohesive properties and its resistance to debonding estimated from the displacement-load curves. This study highlights, as a function of the adhesive properties of the plate/patch interface, the competition between two degradation mechanisms: adhesive damage (through a mechanism of initiation and propagation of patch debonding from the plate) and plate damage (through a phenomenon of crack initiation and propagation emanating from notch). It also highlights, depending on the nature of the interface, four physical parameters: the bending deflection of the repaired plate, the displacement path of the patch-reinforced plate, the debonding resistance and the interfacial shear stresses, characteristic of the adhesive joint damage and their interactions with the interface. This is the originality of this study. Results show that XFEM simulations based on the CZM model allow adequate prediction of the damage of the patch/adhesive/plate assemblies.